DIGITAL TRANSFORMATION CHALLENGES OF EMERGING HOSPITALS IN DIGITAL DISRUPTION - Bawazier, Nisma; Sulistiadi, Wahyu (Transpublika Publisher, 2023)
In the era of Industry 4.0, hospitals face numerous obstacles when it comes to embracing digital disruption. One of the major challenges is dealing with big data. With the increasing amount of data being generated in healthcare, hospitals struggle to effectively manage and analyze this vast amount of information. This paper highlights the challenges faced by hospitals in adopting digital disruption in the era of Industry 4.0. Some of the challenges include big data, scalability, data management, security and privacy, standardization, interoperability and regulation, human factors, implementation costs, networking, integrated IT infrastructure, skills, and device/system heterogeneity. The study suggests that immediate implementation of information technology is required to achieve optimal data integration on a national scale. Various recommendations have been formulated, including improving knowledge management of big data analytics and systems, as well as empowering human resources within the organization. The study calls for more research in Healthcare 4.0, addressing key barriers and identifying trends and gaps that require further exploration.